KAJIAN PROFESIONALISME APARATUR DALAM PENYELENGGARAAN PELAYANAN PUBLIK DI KANTOR CAMAT MALALAYANG KOTA MANAD0 - DEMSY, FREISTY LEA (Sam Ratulangi University, 2014)
ABSTRACT: The organization of public services by officer alweys complainted by the society especially about faster services, the accuracy time for finishing services, mistake services product and any others. The phenomena caused of the sweet officer profesionalism that self bureavcracy, connection with the problems the this research to intend know how profesionalism officer in organizatoin public services in subdistrict Malalayang office manado town.This research is using qualitative method. Informant data sourc in research is officers / PNS in subdistrict Malalayang office taked in style purposive from 28 peoples of PNS. In the office. Gathering data is using interview technic. Whereas data analyzed is using analysis technic qualitative interactive modal from Miles and Hubernan.Besed on research attractived condusions : (1) profesionalism officer of subdistrict Malalayang goverment in organization public services the common was good enough looked from ability aspect / knowleage competence (floor formal education and the relevants with task sector public services). (2) The profesionalism officer of subdistrick Malalayang’s goverment in organization public services the common was feeble looked from ability / expert competence and creativity (education and exercise and the relevantion with task sector public services). (3) Profesionalism officer subdistrict malalayang’s goverment in organization public services the common was good enough looked from aspeck attitude competence in exercise public services.Based on conclusion research output suggested : (1) The officer must gived education and exercise relevant technic / functional. (2) A placing officer at task sector public service sector the heved must attentioned too increase draft profesionalism officer in organization public services.Keywords : the profesionalism officer, public services.